(untitled) (Ágora Journal, 2024)
The article will seek to understand how the idea of ​​“nature” came to govern the political mentality of Brazilian national identity in the 19th century. This identity constitutes, as we know, the basis for representing the unity of individuals with your nature. From then on, the political context of the empire forged a meaning for itself that would highlight this relationship. For example, the reports of José da Cunha Matos, who argued that nature would inhabit the identity of men and reveal their unity, their identification. This idea of ​​“identity” then became linked to the idea of ​​“nature”, thus composing this picture of the culture’s thinking. And fixing man to his land, linking identity and nature, historical and geographic. This would precisely reflect the attempt to overcome the lack of unity in the empire.